Does the internet eraser button for youth delete first amendment right of others? - Kurin, Jaclyn B. (Revista de Investigações Constitucionais, 2017)
Will Facebook and similar posting sites soon come to an end from hefty civil fines and consent decrees? Is Internet discourse at risk? That may be the case if lawmakers succeed in passing the Do Not Track Kids Act. As drafted, the law would require operators of children directed websites to include an eraser button to remove user posted content and would penalize mom and pop run sites unable to afford the financial and technological resources to comply with the mandate. This Note argues that if enacted, the law would constitute a presumptively impermissible burden on Free Speech under the First Amendment and should be subject to strict scrutiny.